Brain Rot and Addiction to Poor Content: Effects of Excessive Mobile Phone Use on Mental Health - Sider, Pr, Kamila; Boulbadaoui, Ali (Journal of Neonatal Surgery, 2025)
This research aims to study the effect of excessive mobile phone use and poor digital content on the brain and mental health, focusing on the phenomenon of "brain rot," which refers to negative changes in brain structure resulting from continuous and passive stimulation from digital content such as fake news, violence, and trivialities. Through a review of current studies, the research discusses how this excessive stimulation affects brain functions, such as memory and concentration, and leads to the emergence of psychological disorders such as anxiety and depression. This research is based on scientific foundations in neuropsychology and clinical psychology to understand the relationship between digital addiction and its short- and long-term effects. It also presents treatment and prevention strategies for these effects, such as cognitive behavioral therapy techniques and techniques to reduce excessive use of technology. In conclusion, we sought to provide solutions for the academic and professional community to improve the use of technology and reduce its negative effects on individuals, especially in light of the increasing psychological challenges associated with the digital age.